Pola Kemitraan Antara Petani Heliconia dengan Sekar Bumi Farm di Desa Kerta Kecamatan Payangan Kabupaten Gianyar - SURIATI, NI NENGAH; DEWI, RATNA KOMALA; DJELANTIK, A.A.A WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract The Pattern of Partnership between Heliconia Farmers and Sekar Bumi Farm in Kerta Village Payangan District Gianyar Regency Heliconia is a type of tropical ornamental plant which is often referred to as ornamental banana. Heliconia is one of ornamental plants developed in Payangan District. Heliconia farmers cooperated with Sekar Bumi Farm in provide infrastructure, market access, and could meet production needs for Sekar Bumi Farm so that it can provide benefits for both parties partners. The purpose of this research was  to determine: (1) the mechanisms of partnership, (2) the success of the partnership, (3) the benefits of the partnership, and (4) constraints faced in partnership. Respondents of this research was 40 % of the 72 members of Amerta Jati, Jati Mekar and Jati Mulia farmers group. Data was obtained through observation method, documentation study, and interview using questionnaires. Qualitative and quantitative data analysis were used in this research. The results indicated that (1) Form of implementation is done in partnership with Sekar Bumi Farm using plasma core pattern (2) mechanism of partnership between farmers with Sekar Bumi Farm originated from Sekar Bumi Farm to approach farmers to be willing to partner, creating a cooperation agreement concerning the rights and obligations of each party, and agree on the agreements (3) ratio of farmer’s profit increased before partnering was 0.98 to 1.34 after joining partnership, (4) benefits of the partnership on the technical aspects, namely Sekar Bumi Farm provide information to farmers, the economic aspect is a guaranteedmarket and increasing farm income, and the social aspect that is the desireof continuity of cooperation, and (5) Constraints in the partnership is unstable market prices, harvesting is not on schedule, weather factors affecting production, and the number and role of extension worker of the Sekar Bumi Farm is still less than optimal. Keywords: Partnership, Farmer, Heliconia, Sekar Bumi Farm